The effects of Tai Ji Quan training on limits of stability in older adults - Li F (Dove Medical Press, 2014)
Fuzhong Li1,2 1Oregon Research Institute, Eugene, OR, USA; 2Shanghai University of Sport, Shanghai, People’s Republic of ChinaBackground: Limits of stability, defined as the ability to maintain the center of gravity within the boundary of the base of support, is critically important for older adults in performing their activities of daily living. However, few exercise programs specifically tailored to enhance limits of stability exist. The primary purpose of this study was to determine whether a therapeutically designed intervention, Tai Ji Quan: Moving for Better Balance (TJQMBB), could improve limits of stability in older adults. A secondary purpose was to examine concomitant change in limits of stability and physical performance as a result of the intervention.Methods: A single-group design was used in which 145 community-dwelling older adults (average age: 75 years) were enrolled in TJQMBB classes, participating twice weekly for 48 weeks. Primary outcome measures were three indicators of limits of stability (LOS) (endpoint excursion, movement velocity, and directional control), with secondary measures of physical performance being Timed Up and Go and 50-foot speed walk (in seconds), which were assessed at baseline, 24 weeks, and 48 weeks. Changes in the repeated measures of outcome variables were analyzed via latent curve analysis.Results: At 48 weeks, a significant rate of change (improvement) over time was observed in the three limits of stability indicators (endpoint execution: 8.30% LOS, P<0.001; movement velocity: 0.86 degrees/second, P<0.001; directional control: 6.79% of 100, P<0.001); all reached a threshold of real change as judged by the minimal detectable change values. Improvements in the three limits of stability measures were concomitantly correlated with improved (reduced times) performance scores in the Timed Up and Go (-0.30, -0.45, and -0.55, respectively) and 50-foot walk (-0.33, -0.49, and -0.41, respectively).Conclusion: In this single-group study, community-dwelling older adults trained through TJQMBB significantly improved their limits of stability, providing preliminary support for the use of TJQMBB as a therapeutic modality for enhancing functional activities in older adults. Keywords: mobility, balance, activities of daily living, exercise, elderly